The Efficacy of Β-Glucans Enzyme and Secondary Metabolites of the White Fungus (Agaricus Bisporus) as Inhibitory Agents for Lung Cancer Cells - Oubid, Sarah Hashim (American Journal of Biology and Natural Sciences, 2026)
β-glucans are long- or short-chain polymers made up of glucose subunits, with β-1,3 and β-1,6 bonds, responsible for the linear and branched structures respectively, found in the cell walls of the fungus Agaricus bisporus, which have an effective role in immune modulation and as an anti-inflammatory using β-glucans extracted from the white fungus. Qualitative inferential studies were conducted on the primary and secondary metabolites of A. bisporus extract. The results indicated that A. bisporus contains phenolic compounds, flavonoids, tannins, alkaloids, and carbohydrates, but the proportions of alkaloids, saponins, tannins, and reducing sugars were the highest compared to phenols and flavonoids. The active compounds in the extract of A. bisporus fungus were also determined, namely ash, moisture, oil, fiber, and protein. The results showed that the concentrations of fiber, moisture, protein, and oil were 14.34%, 12.18%, 9.96%, and 7.99%, respectively. The rate of cancer cell death was determined by the effect of β-glucans enzyme on lung cancer cell line A549 pass 21 after 24 hours of treatment. Seven different concentrations of the enzyme were used, and the inhibition rates of the seven concentrations were compared for MB 231 lung cancer cells. All concentrations of β-glucans enzyme caused a significant inhibition rate of lung cells. The results showed that a concentration of 1 mg/ml achieved a significant inhibition ratio (IR) of 70.54% in the lung cancer cell line, while the same concentration showed an inhibition ratio of 98.14% in the normal cell line.